electrode
Patent Information
- Application Number
- CN202280050755.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-30
- Filing Date
- 2022-06-10
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-06-10
AI Technical Summary
[0018]本发明的电极的芯材与复合材料层的界面电阻低,且复合材料层相对于芯材的粘接力高。
Smart Images

Figure CN117751461B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to electrodes, and more specifically, to electrodes for secondary batteries. Background Technology
[0002] Electrodes in secondary batteries such as lithium-ion batteries typically include a core material that is a metal foil, and a composite material layer comprising an active material, a conductive material, and a binder material formed on the core material. Furthermore, electrodes with a conductive intermediate layer between the core material and the composite material layer are also known (see Patent Documents 1-5). This intermediate layer can, for example, reduce the resistance at the interface between the core material and the composite material layer, thus helping to improve the battery's output characteristics. It should be noted that Patent Documents 1-5 describe the use of two types of particles with different particle sizes as the conductive particles contained in the intermediate layer.
[0003] However, conventional electrodes are typically manufactured using a wet process, where an electrode composite slurry is coated onto the surface of a core material, followed by drying and compression of the coating. This process presents a technical problem: the migration of binder materials can easily occur during the drying process. When binder material migration occurs, the amount of binder material on the surface side of the composite layer increases compared to the core side, leading to a deviation in the distribution of binder material along the thickness direction of the composite layer. In recent years, research has also been conducted on a dry process for manufacturing electrodes, involving calendering the electrode composite material into sheets to create electrode composite sheets, and then bonding these sheets to the core material.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-109080
[0007] Patent Document 2: Japanese Patent No. 5098954
[0008] Patent Document 3: Japanese Patent No. 4352349
[0009] Patent Document 4: Japanese Patent No. 5648869
[0010] Patent Document 5: Japanese Patent No. 6239936 Summary of the Invention
[0011] The problem the invention aims to solve
[0012] As described above, providing a conductive interlayer between the electrode core and the composite material layer is effective in reducing the interfacial resistance between the core and the composite material layer. In particular, the interfacial resistance tends to increase in electrodes manufactured using a dry process; therefore, providing a conductive interlayer can be considered one of the effective means of reducing interfacial resistance. On the other hand, reducing the interfacial resistance and increasing the adhesion between the composite material layer and the core surface to improve the peel strength of the composite material layer are important technical problems. However, achieving both reduced interfacial resistance and increased adhesion between the composite material layer and the core material is not easy. The technologies disclosed in Patent Documents 1-5 still have room for improvement in terms of balancing these relevant characteristics.
[0013] The purpose of this invention is to provide an electrode with low interfacial resistance between the core material and the composite material layer and high adhesion between the composite material layer and the core material.
[0014] Solution for solving the problem
[0015] The electrode according to one aspect of the present invention is characterized in that it comprises a core material, a composite material layer disposed on the core material, and a conductive intermediate layer disposed between the core material and the composite material layer. The composite material layer comprises an active material and a first binder material, and the intermediate layer comprises a conductive material and a second binder material. The conductive material has a particle size distribution comprising a first peak with a particle size in the range of 0.005 to 0.07 μm and a second peak with a particle size in the range of 0.5 to 10 μm. The content of particles constituting the first peak is 1 to 40% by mass of the conductive material. The second binder material is mainly composed of a thermoplastic resin with a melting point of 100 to 200°C, and its composition is different from that of the first binder material.
[0016] Another aspect of the electrode of the present invention is characterized in that it comprises a core material, a composite material layer disposed on the core material, and a conductive intermediate layer disposed between the core material and the composite material layer. The composite material layer comprises an active material and a first binder material. The intermediate layer comprises a conductive material and a second binder material. The conductive material comprises first particles with a particle size of 0.005 to 0.07 μm and forming a beaded aggregate structure, and second particles with a particle size of 0.5 to 10 μm. The content of the first particles is 1 to 40% by mass of the conductive material. The second binder material is mainly composed of a thermoplastic resin with a melting point of 100 to 200°C, and its composition is different from that of the first binder material.
[0017] The effects of the invention
[0018] The electrode of the present invention has a low interfacial resistance between the core material and the composite material layer, and a high adhesive force between the composite material layer and the core material. Attached Figure Description
[0019] Figure 1A diagram illustrating a cross-section of an electrode as an example of an implementation.
[0020] Figure 2 for Figure 1 Enlarged view of part A in the image.
[0021] Figure 3 In the electrode manufacturing process, which is an example of an implementation, (a) is a diagram showing the mixing process of the composite material raw materials, and (b) is a diagram showing the calendering process of the composite material.
[0022] Figure 4 A diagram illustrating the bonding process of composite material sheets.
[0023] Figure 5 A diagram illustrating a cross-section of the intermediate layer of a comparative example.
[0024] Figure 6 A diagram illustrating a cross-section of the intermediate layer of a comparative example. Detailed Implementation
[0025] Hereinafter, an example of an embodiment of the electrode of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the configuration formed by selectively combining the various embodiments and modifications described below is included in the present invention.
[0026] The electrode of the present invention is suitable for use in non-aqueous electrolyte secondary batteries such as lithium-ion batteries, but can also be used in energy storage devices such as batteries or capacitors containing aqueous electrolytes. The following description will focus on the application of the electrode, particularly the positive electrode, in a non-aqueous electrolyte secondary battery.
[0027] Figure 1 A cross-sectional view of electrode 10, as an example of an embodiment, is shown schematically. Figure 1 As shown, the electrode 10 includes a core material 11, a composite material layer 12 disposed on the core material 11, and a conductive intermediate layer 13 disposed between the core material 11 and the composite material layer 12. The electrode 10 has the intermediate layer 13 and the composite material layer 12 on both sides of the core material 11. The thickness of the composite material layer 12 on one side of the core material 11 is, for example, 30 μm to 120 μm, preferably 50 μm to 100 μm. The electrode 10 can be a long strip electrode constituting a wound electrode body, or a rectangular electrode constituting a stacked electrode body.
[0028] The core material 11 can be a metal foil, a thin film with a metal layer formed on its surface, or the like. The thickness of the core material 11 is, for example, 5 μm to 20 μm. In the case of a positive electrode, the core material 11 can be a metal foil with aluminum as the main component. In the case of a negative electrode, a metal foil with copper as the main component can be used. In this specification, the main component refers to the component with the highest mass ratio. The core material 11 can be an aluminum foil that is actually 100% aluminum, or a copper foil that is actually 100% copper.
[0029] The composite material layer 12, also known as the active material layer, comprises an active material and a binder material (first binder material). The composite material layer 12 may also contain a conductive material, particularly when the electrode 10 is a positive electrode; in such cases, the composite material layer 12 preferably contains a conductive material. Examples of conductive materials include carbon black, acetylene black, Ketjen black, carbon nanotubes, graphite, and other carbon materials. The content of the conductive material relative to the mass of the composite material layer 12 is, for example, 0.5 to 5% by mass. Details will be described later, but it is preferable that the composite material layer 12 is formed from a composite material sheet 12z manufactured using a dry process, and that the composite material layer 12 contains a fibrous binder material.
[0030] The preferred conductive material contained in the composite material layer 12 is conductive particles with a particle size of 0.005 to 0.07 μm that form a beaded aggregate structure. The conductive material of the composite material layer 12 can be the same as or the same as the first particle 16 of the intermediate layer 13 described later. Since the composite material layer 12 and the intermediate layer 13 contain the aforementioned conductive particles, a beaded aggregate structure can also be formed at the interface between the composite material layer 12 and the intermediate layer 13, making it easy to achieve conductivity at the interface between the composite material layer 12 and the intermediate layer 13.
[0031] The positive electrode active material (positive electrode active material) is typically a lithium transition metal composite oxide. Examples of metal elements contained in the lithium transition metal composite oxide include Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, and W. Preferably, it contains at least one element selected from Ni, Co, and Mn. The content of the positive electrode active material relative to the mass of the composite layer 12 is preferably 85–99% by mass, more preferably 90–99% by mass (the content of the negative electrode active material is also the same as the content of the positive electrode active material).
[0032] The positive electrode active material is a secondary particle formed by the aggregation of multiple primary particles. The median particle size (D50) of the positive electrode active material on a volume basis is preferably 3–30 μm. D50 refers to the particle size at which the cumulative frequency reaches 50% from the smallest particle size in the volume-based particle size distribution; it is also called the median diameter. The particle size distribution of the positive electrode active material can be determined using a laser diffraction-based particle size distribution measuring device (e.g., Microtrac BelCo., Ltd., MT3000II) with water as the dispersion medium.
[0033] It should be noted that the active material of the negative electrode can be, for example, natural graphite such as flake graphite, block graphite, and amorphous graphite, or artificial graphite such as block graphite (MAG) and graphitized mesophase carbon microspheres (MCMB), and other carbon-based active materials. The negative electrode active material can also contain active materials such as Si and Sn alloyed with lithium.
[0034] The fibrous binder material contained in the composite layer 12 can be produced, for example, by fibrillating fine polytetrafluoroethylene (PTFE) particles that are fibrillable by using a dry mill such as a jet mill. The average particle size of the PTFE particles is not particularly limited, but is preferably 100–500 μm, more preferably 100–400 μm. The average particle size of the PTFE particles can be determined by observing the PTFE particles using a scanning electron microscope (SEM). Specifically, the shapes of 100 randomly selected particles are determined, and the major diameter (longest diameter) of each of the 100 particles is calculated, with their average value taken as the average particle size.
[0035] The content of the fibrous binder material relative to the mass of the composite layer 12 is, for example, 0.5% to 5% by mass. The fibrous binder material adheres to the surface of the active material particles and intertwines with the active material. That is, the active material is held in place by the fibrous binder material, thereby forming the layer structure of the composite layer 12. It should be noted that, in addition to the fibrous binder material, the composite layer 12 may also contain particulate binders such as non-fibrillated polyvinylidene fluoride (PVdF).
[0036] When the composite material layer 12 is divided into three equal parts along its thickness direction, designated as region 1, region 2, and region 3 starting from the core material 11 side, the content (a) of the fibrous binder material in region 1, the content (b) of the fibrous binder material in region 2, and the content (c) of the fibrous binder material in region 3 preferably satisfy (ca) / (a+b+c)≤±10%, more preferably satisfying (ca) / (a+b+c)≤±5%. That is, the fibrous binder material is substantially uniformly present throughout the entire composite material layer 12, rather than being locally present in a part of the composite material layer 12. It should be noted that when the composite material layer 12 is a positive electrode additive layer, the density of the positive electrode active material in the composite material layer 12 is preferably 3.3 g / cc to 4.0 g / cc.
[0037] Below, refer to Figure 2 The composition of the intermediate layer 13 will be explained in detail. Figure 2 for Figure 1 Enlarged view of part A in the image.
[0038] like Figure 2 As shown, the intermediate layer 13 is sandwiched between the core material 11 and the composite material layer 12, reducing the interfacial resistance between the core material 11 and the composite material layer 12, and increasing the adhesion of the composite material layer 12 to the core material 11. That is, the intermediate layer 13 functions as both a conductive layer and an adhesive layer. The intermediate layer 13 comprises a conductive material 14 and an adhesive material 15 (a second adhesive material). The thickness of the intermediate layer 13 is, for example, 1 μm to 10 μm. The conductive material 14 in the intermediate layer 13 comprises two types of conductive particles (a first particle 16 and a second particle 17) with different particle sizes. This improves the adhesion of the composite material layer 12 to the core material 11 and ensures a good conductive path, thereby reducing the interfacial resistance between the core material 11 and the composite material layer 12.
[0039] The content of conductive material 14 is preferably 50-90% by mass of the intermediate layer 13, more preferably 60-90% by mass or 65-85% by mass. If the content of conductive material 14 is within this range, it is easy to achieve both low interfacial resistance and high adhesion at the interface between the core material 11 and the composite material layer 12. In this embodiment, the intermediate layer 13 is actually composed only of conductive material 14 and adhesive material 15. The content of adhesive material 15 is preferably 10-50% by mass of the intermediate layer 13, more preferably 10-40% by mass or 15-35% by mass.
[0040] The conductive material 14 has a particle size distribution comprising a first peak with a particle size ranging from 0.005 to 0.07 μm and a second peak with a particle size ranging from 0.5 to 10 μm. The particle size distribution of the conductive material 14 is a volume-based particle size distribution, which can be determined by measuring the diameter of the circumcircle of the particles from a cross-sectional SEM image of the intermediate layer 13. It should be noted that when the particle size distribution of the conductive material 14 powder added to the intermediate layer 13 is measured using a laser diffraction-based particle size distribution measuring device, the same values as those obtained from the cross-sectional SEM image can also be obtained. The particle size range of the first peak is more preferably 0.02 to 0.04 μm. The particle size range of the second peak is more preferably 2 to 4 μm.
[0041] Furthermore, the conductive material 14 includes a first particle 16 with a particle size of 0.005 to 0.07 μm and forming a beaded aggregate structure, and a second particle 17 with a particle size of 0.5 to 10 μm. The beaded aggregate structure is also referred to as a textured structure. In this embodiment, the first particle 16 forms the aforementioned first peak, and the second particle 17 forms the aforementioned second peak. The intermediate layer 13 is formed using the first particle 16 and the second particle 17, whose volume reference D50 values measured by a laser diffraction-type particle size distribution measuring device are different. The D50 of the first particle 16 is 0.005 to 0.07 μm, and the D50 of the second particle 17 is 0.5 to 10 μm. The particle size range of the first particle 16 is more preferably 0.02 to 0.04 μm. The particle size range of the second particle 17 is more preferably 2 to 4 μm.
[0042] The content of the first particle 16 is 1 to 40% by mass of the conductive material 14. The conductive material 14 may also contain a third particle that is not part of the first particle 16 and the second particle 17, but in this embodiment, the conductive material 14 is actually composed only of the first particle 16 and the second particle 17, and the content of the second particle 17 is 60 to 99% by mass of the conductive material 14. By using the conductive material 14 having the above-described particle size distribution and controlling the mixing ratio of the first particle 16 (as a small particle) and the second particle 17 (as a large particle) within this range, the resistance at the interface between the core material 11 and the composite material layer 12 can be reduced, and high adhesion can be ensured.
[0043] The content of the first particle 16 relative to the mass of the conductive material 14 is more preferably 3 to 35% by mass, and particularly preferably 5 to 30% by mass. When the content of the first particle 16 is less than 1% by mass, the adhesion of the composite material layer 12 to the surface of the core material 11 decreases, making it difficult to ensure sufficient peel strength. On the other hand, when the content of the first particle 16 exceeds 40% by mass, the interfacial resistance between the core material 11 and the composite material layer 12 increases significantly. Details will be described later, but since the second particle 17, being a large particle, is difficult to be encapsulated by the adhesive material 15, adding a specified amount of the second particle 17 can form a good conductive path, thereby reducing the interfacial resistance. In addition, since the first particle 16, being a small particle, has a high affinity with the adhesive material 15, it is believed that adding a specified amount of the first particle 16 improves the peel strength.
[0044] The conductive material 14, for example, comprises particles with a particle size of 0.5 to 10 μm and an average aspect ratio of 10 to 40. As described above, the particles with a particle size of 0.5 to 10 μm are the second particles 17, and therefore the average aspect ratio of the second particles 17 can be considered to be 10 to 40. The aspect ratio of the conductive material 14 can be obtained by measuring the major and minor axes of the particles of the conductive material 14 from a cross-sectional SEM image of the intermediate layer 13, and dividing the major axis by the minor axis. The average aspect ratio is calculated by averaging the aspect ratios obtained for 100 randomly selected particles. In addition, the average aspect ratio of the first particle 16 is less than 10, preferably less than 5.
[0045] The conductive material 14 is a particle composed of a conductive material. A preferred example of the conductive material 14 is a carbon material. Specific examples of carbon materials include carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphite. The first particle 16 and the second particle 17 may be composed of the same type of carbon material or different types of carbon materials. Compared to the larger second particle 17, the smaller first particle 16 has a larger specific surface area per unit mass; the BET specific surface area of the first particle 16 is, for example, 100–150 m². 2 / g.
[0046] The adhesive material 15 is mainly composed of a thermoplastic resin with a melting point of 100-200°C, and its composition differs from that of the adhesive material of the composite layer 12. The adhesive material 15 is melted or softened, for example, in the bonding process described later, and firmly bonded to the core material 11 and the composite layer 12. Regarding the composite layer 12, it is preferable that it is mainly composed of a resin that is difficult to melt or soften in the bonding process. As a preferred combination of adhesive materials for each layer, the adhesive material for the composite layer 12 is fibrillated PTFE, and the adhesive material 15 for the intermediate layer 13 is a homopolymer or copolymer of vinylidene fluoride.
[0047] The binder material 15 is more abundant around the first particle 16, for example, in the intermediate layer 13. As described above, the first particle 16 has a larger BET specific surface area than the second particle 17, and it is also aggregated in a beaded shape, thus exhibiting a high affinity for the binder material 15, which is abundant around the first particle 16. In this embodiment, the proportion of the surface of the first particle 16 covered by the binder material 15 is greater than the proportion of the surface of the second particle 17 covered by the binder material 15. The greater abundance of the binder material 15 around the first particle 16 can be confirmed by mapping analysis of the constituent elements of the binder material 15 using energy-dispersive X-ray (EDX) from an SEM image of the surface of the intermediate layer 13.
[0048] The intermediate layer 13 can be formed by coating the surface of the core material 11 with a slurry containing conductive material 14 and binder material 15, and then drying the coating. The conductive material 14 uses first particles 16 with a volumetric D50 of 0.005–0.07 μm and second particles 17 with a volumetric D50 of 0.5–10 μm. An example of the dispersion medium for the slurry is N-methyl-2-pyrrolidone (NMP). It should be noted that the intermediate layer 13 can also be formed on the surface of the core material 11 using dip coating or spray coating methods.
[0049] The following is a reference Figure 3 and Figure 4 The manufacturing method of electrode 10 will be explained below. An example of the manufacturing method of the positive electrode will be given below, but the same manufacturing method can also be applied to the manufacturing of the negative electrode. Figure 3 (a) shows the mixing process of mixing composite material raw materials to produce composite material 20. Figure 3 (b) shows the calendering process of calendering composite material 20 to produce composite material sheet 12z. Figure 4 The bonding process is shown in which a strip-shaped core material 11z is bonded to a composite material sheet 12z.
[0050] like Figure 3 As shown, the composite material sheet 12z is manufactured using a dry process with a composite material 20 having a solid content concentration of 100%. Details will be described later, but the electrode 10 is manufactured by bonding the composite material sheet 12z to both sides of a core material 11z with an intermediate layer 13 formed thereon. In the dry process, no solvent is used when mixing the composite material raw materials to produce the composite material 20 with a solid content concentration of 100%. In the mixing step, the active material, fibrous binder, and conductive material are mixed using a mixer 30 to produce the composite material 20.
[0051] The mixer 30 can be a conventionally known mechanical mixing mixer capable of imparting mechanical shear force. Specific examples of the mixer 30 include shredders, pin mills, bead mills, microparticle compounding devices (devices that generate shear force between a specially shaped rotor rotating at high speed inside a tank and an impact plate), granulators, twin-screw extrusion mixers, planetary mixers, and other similar mixers. Among these, shredders, microparticle compounding devices, granulators, or twin-screw extrusion mixers are preferred. During the mixing process, composite material raw materials can be mixed, and fibrous binders can be further fibrillated.
[0052] The processing time of the mixing process (the time to apply shear force to the composite material raw material) is preferably within a few minutes, for example, 0.5 to 10 minutes. If the processing time is too long, the amount of conductive material encased in the fibrous binder may increase, leading to a decrease in the conductivity of the composite sheet 12z. The mixing process may include a process of mixing the active material with the conductive material to create a coating active material, and a process of mixing the coating active material with the fibrous binder. By using a coating active material created by mixing the active material with the conductive material, the mixing time between the coating active material and the fibrous binder can be shortened. This reduces the amount of conductive material encased in the fibrous binder.
[0053] Dry mixing of active materials and conductive materials can also be achieved using mechanical fusion. By applying mechanical fusion, the bonding force between the conductive material and the particle surface of the active material is enhanced. Examples of mechanical fusion reaction devices include the Nobilta (registered trademark) pulverizer or MECHANO FUSION (registered trademark) pulverizer manufactured by Hosokawa Micron Corporation, the Hybridizer (registered trademark) pulverizer manufactured by Nara Machinery Manufacturing Co., Ltd., the BALANCE GRAN manufactured by FREUND-TURBOCORPORATION, and the COMPOSI manufactured by NIPPON COKE & ENGINEERING.CO.,LTD.
[0054] The composite material 20 obtained from the mixing process is formed into sheets in the calendering process. Figure 3 In the example shown in (b), the composite material 20 is calendered using two rollers 31 to obtain a composite material sheet 12z. The two rollers 31 are arranged at a predetermined interval and rotate in the same direction. The composite material 20 is supplied to the gap between the two rollers 31, whereby it is compressed and stretched into a sheet shape by the two rollers 31. The two rollers 31, for example, have the same diameter. The composite material sheet 12z can pass through the gap between the two rollers 31 multiple times, or it can be hot-pressed using heated rollers 31.
[0055] The thickness of the composite sheet 12z can be controlled, for example, by the spacing between the two rollers 31, the circumferential speed, and the number of stretching processes. In the calendering process, two rollers 31 with a circumferential speed ratio differing by more than twice can be used to form the composite material 20 into a sheet. By making the circumferential speed ratio of the two rollers 31 different, it is easier to thin the composite sheet 12z, thus increasing productivity. Furthermore, it is preferable to further compress the composite sheet 12z to increase its density. In this compression process, for example, a linear pressure of 1 to 3 t / cm can be applied.
[0056] like Figure 4 As shown, by bonding the composite material sheet 12z to the elongated core material 11z, a composite material layer 12 formed by the composite material sheet 12z is provided on the surface of the core material 11z. Figure 4 The diagram shows a state where the composite sheet 12z is joined only on one side of the core material 11z, but the composite sheet 12z can be joined on both sides of the core material 11z. Two composite sheets 12z can be joined to both sides of the core material 11z simultaneously, or one sheet can be joined to one side of the core material 11z and the other sheet can be joined to the other side.
[0057] In the bonding process, two rollers 32 are used to bond the composite material sheet 12z to the surface of the core material 11z. For example, the temperature of the two rollers 32 is 50°C to 300°C, preferably 100°C to 200°C, and the linear pressure applied by the two rollers 32 is 0.1 to 2 t / cm. The core material 11z with the composite material sheet 12z bonded to both sides is cut to a predetermined electrode size, thereby obtaining an electrode 10 having the above-described configuration. An intermediate layer 13 is formed on both sides of the core material 11z supplied for the bonding process, and the composite material sheet 12z is bonded to both sides of the core material 11z through the intermediate layer 13. As described above, the intermediate layer 13 is formed by coating both sides of the core material 11z with a slurry containing two conductive materials and a bonding material, drying the coating film, and calendering it.
[0058] Example
[0059] The present invention will be further illustrated by the following embodiments, but the present invention is not limited to these embodiments.
[0060] <Example 1>
[0061] [Formation of the intermediate layer]
[0062] A conductive material was prepared by mixing carbon black (first particle) with a volumetric D50 (D50) of 0.023 μm and an average aspect ratio of 1 to 1.3, and carbon black (second particle) with a D50 of 2.4 μm and an average aspect ratio of 24, at a mass ratio of 25:75. This conductive material was then mixed with a homopolymer of vinylidene fluoride (PVdF) at a mass ratio of 83:17, using NMP as a dispersion medium to prepare a slurry. Next, this slurry was coated onto the surface of an electrode core material formed from an aluminum foil with a thickness of 14.4 μm. After drying the coating, it was calendered using calendering rolls, thereby forming an intermediate layer on the core material surface containing two types of carbon black with different D50s and PVdF. It should be noted that the core material with intermediate layers formed on both sides was cut to a specified electrode size.
[0063] [Fabrication of positive electrode composite sheet]
[0064] Using NOB300-Nobilta (registered trademark) manufactured by Hosokawa Micron Corporation, 1000g of lithium transition metal composite oxide was mixed with 10g of carbon black for 5 minutes to prepare a carbon-coated positive electrode active material with carbon black adhering to the surface of the composite oxide particles. This carbon-coated positive electrode active material was then added to a fibrous binder obtained by fibrillating PTFE particles at a mass ratio of 101:0.8 in a Wonder crusher manufactured by Osaka Chemical Co., Ltd., and mixed at room temperature at a speed of 5 rpm for 5 minutes. It should be noted that the maximum speed of the Wonder crusher at scale 10 is 28000 rpm.
[0065] Through the above mixing process, a cathode composite material in which carbon-coated positive electrode active material and fibrous binder are uniformly dispersed is obtained. The solid content concentration of the obtained cathode composite material is 100%. The cathode composite material is then calendered between two rollers to produce a cathode composite sheet. The circumferential speed ratio of the two rollers is set to 1:3, and the thickness of the cathode composite sheet is adjusted to 100-120 μm. Next, the obtained cathode composite sheet is compressed between two rollers at room temperature.
[0066] [Positive electrode manufacturing (bonding process)]
[0067] The aforementioned positive electrode composite sheet is placed on a core material with intermediate layers formed on both sides. Two rollers at room temperature (25°C) are used to press the laminate of the positive electrode composite sheet and the core material (linear pressing: 0.5 t / cm), thereby obtaining a positive electrode A1 with intermediate layers and a positive electrode composite layer (positive electrode composite sheet) on both sides of the core material. The thickness of the positive electrode A1 is adjusted to 170–180 μm. The density of the positive electrode active material in the positive electrode composite layer is adjusted to 3.7 g / cc. It should be noted that when the composite layer is divided into three equal parts along its thickness direction, designated as region 1, region 2, and region 3 from the core material side, and the content of fibrous binder material in region 1 (a), region 2 (b), and region 3 (c) is calculated, (ca) × 100 / (a + b + c) = 1%.
[0068] For the positive electrode A1, the interfacial resistance and peel strength were measured using the following method. Additionally, the distribution of the binder material in the interlayer (whether any localized areas existed) was confirmed. The measurement results, along with the composition of the interlayer, are presented in Table 1 as the mass percentage of fluorine (F mass%).
[0069] [Measurement of interfacial resistance]
[0070] For the positive electrode A1, the interface resistance was measured using an electrode resistance meter (device name: XF057) manufactured by Hioki Electric Co., Ltd. The measuring current was set to 100μA and the voltage range was set to 0.5V.
[0071] [Evaluation of peel strength]
[0072] A 10mm × 90mm positive electrode composite layer of positive electrode A1 was adhered to double-sided adhesive tape (NICHIBAN Co., Ltd. NICETACK NW-20) bonded to the test stage. At 25°C, using an A&D Company, Limited material testing machine (ORIENTEC RTC-1150A), one end of positive electrode A1 was pulled vertically relative to the test stage at a constant speed of 20mm / min. The load at which the positive electrode composite layer peeled from the core material was measured and defined as the peel strength of the composite layer.
[0073] [Distribution of adhesive material in the intermediate layer]
[0074] In the SEM image of the intermediate layer surface taken before the formation of the composite layer, three locations were selected on the surface of the second particle, and three locations were selected in the area excluding the surface of the second particle. For the six selected locations, carbon and fluorine mapping analysis was performed using EDX. The mass ratio of fluorine in the six selected locations was calculated using image analysis software. The average values of the three locations on the surface of the second particle and the three locations in the area excluding the surface of the second particle were calculated separately. It should be noted that the area excluding the surface of the second particle corresponds to the area surrounding the first particle. A magnification range of 2000–20000x was set as a suitable magnification for observation.
[0075] <Example 2>
[0076] In the formation of the intermediate layer, the mass ratio of conductive material to binder material was changed to 71:29. Otherwise, the positive electrode A2 was fabricated in the same manner as in Example 1, and the above performance evaluation was performed.
[0077] <Example 3>
[0078] In the formation of the intermediate layer, the mass ratio of the first particle to the second particle was changed to 10:90. Otherwise, the positive electrode A3 was made in the same manner as in Example 2, and the above performance evaluation was performed.
[0079] <Example 4>
[0080] In the formation of the intermediate layer, carbon black with a D50 of 1.8 μm and an average aspect ratio of 18 was used as the second particle. Otherwise, the positive electrode A4 was made in the same manner as in Example 2, and the above performance evaluation was performed.
[0081] <Example 5>
[0082] In the formation of the intermediate layer, carbon black with a D50 of 3.6 μm and an average aspect ratio of 36 was used as the second particle. Otherwise, the positive electrode A5 was made in the same manner as in Example 2, and the above performance evaluation was performed.
[0083] <Example 6>
[0084] In the formation of the intermediate layer, carbon black with a D50 of 0.036 μm and an average aspect ratio of 1 to 1.3 was used as the first particle. Otherwise, the positive electrode A6 was made in the same manner as in Example 2, and the above performance evaluation was performed.
[0085] <Comparative Example 1>
[0086] In the formation of the intermediate layer, the first particle is not used, and only the second particle is used as the conductive material. Otherwise, the positive electrode B1 is made in the same manner as in Example 2, and the above performance evaluation is performed.
[0087] <Comparative Example 2>
[0088] In the formation of the intermediate layer, the mass ratio of the first particle to the second particle was changed to 75:25. Otherwise, the positive electrode B2 was made in the same manner as in Example 1, and the above performance evaluation was performed.
[0089] <Comparative Example 3>
[0090] In the formation of the intermediate layer, carbon black with a D50 of 22.9 μm and an average aspect ratio of 5 was used as the second particle. Otherwise, the positive electrode B3 was made in the same manner as in Comparative Example 2, and the above performance evaluation was performed.
[0091] <Comparative Example 4>
[0092] In the formation of the intermediate layer, the mass ratio of the first particle to the second particle was changed to 50:50. Otherwise, the positive electrode B4 was made in the same manner as in Comparative Example 2, and the above performance evaluation was performed.
[0093] [Table 1]
[0094]
[0095] As shown in Table 1, compared to the positive electrode of the comparative examples, the positive electrode of the embodiments has a lower interfacial resistance between the core material and the composite material layer, and a higher peel strength of the composite material layer. That is, the positive electrode of the embodiments can achieve both low interfacial resistance and high peel strength. On the other hand, the positive electrodes of the comparative examples cannot achieve both of these characteristics. The positive electrode of Comparative Example 1, which has an intermediate layer that does not contain a first particle (a small particle), has low peel strength and high interfacial resistance. The positive electrode of Comparative Example 2, which has an intermediate layer containing a large number of first particles, has high peel strength, but cannot reduce the interfacial resistance. Compared to the positive electrode of Comparative Example 2, the positive electrode of Comparative Example 3, which has an increased particle size of the second particle in the intermediate layer, has significantly lower peel strength and higher interfacial resistance. The positive electrode of Comparative Example 4 also cannot sufficiently reduce the interfacial resistance.
[0096] Figure 5 The diagram schematically shows a cross-section of a positive electrode having a comparative example that does not include an intermediate layer 100 containing a second particle 17, which is a large particle. Figure 5 The intermediate layer 100 shown has a structure similar to that of the intermediate layers in Comparative Examples 2 and 3 in Comparative Examples 1 to 4. In the intermediate layer 100, it can be considered that the first particle 16 is trapped by the adhesive material 15, thereby inhibiting the conductive path and increasing the interfacial resistance. That is, when the second particle 17 is absent in the intermediate layer or when the content of the second particle 17 is less than a specified amount, a good conductive path cannot be formed, and the interfacial resistance increases significantly.
[0097] Figure 6This diagram schematically illustrates a positive electrode cross-section of Comparative Example 1, which includes an intermediate layer 101 that does not contain the first particle 16. In the intermediate layer 101, due to the low affinity between the first particle 16 and the adhesive material 15, the adhesive strength of the intermediate layer 101 decreases, while the interfacial resistance increases. That is, when the first particle 16 is absent from the intermediate layer or when the content of the first particle 16 is below a predetermined amount, not only does the peel strength of the composite material layer decrease significantly, but the interfacial resistance also increases significantly.
[0098] In contrast, according to Figure 3 The intermediate layer 13 shown (the intermediate layer of the embodiment) can form a good conductive path through the large second particle 17 that is not encased in the adhesive material 15, thereby reducing the interfacial resistance, and can achieve high peel strength through the small first particle 16 that has high affinity with the adhesive material 15. By adding the first particle 16 and the second particle 17 to the intermediate layer 13 and controlling the mass ratio of each particle within a specific range, the interaction between the first particle 16 and the second particle 17 can be efficiently expressed, achieving a balance between low interfacial resistance and high peel strength.
[0099] Explanation of reference numerals in the attached figures
[0100] 10 Electrode; 11 Core material; 11z Strip core material; 12 Composite material layer; 12z Composite material sheet; 13 Intermediate layer; 14 Conductive material; 15 Adhesive material; 16 First particle; 17 Second particle; 20 Composite material; 30 Mixer; 31, 32 Rollers
Claims
1. An electrode comprising: a core material, a composite material layer disposed on the core material, and a conductive intermediate layer disposed between the core material and the composite material layer. The composite material layer comprises an active substance and a first binder material. The intermediate layer comprises a conductive material and a second adhesive material. The conductive material has a particle size distribution comprising a first peak in the range of 0.005–0.07 μm and a second peak in the range of 0.5–10 μm. The content of the first particle constituting the first peak is 1 to 40% by mass of the conductive material. The average aspect ratio of the second particle constituting the second peak is 10 to 40. The second adhesive material is mainly composed of thermoplastic resin with a melting point of 100-200°C, and its composition is different from that of the first adhesive material.
2. An electrode comprising: a core material, a composite material layer disposed on the core material, and a conductive intermediate layer disposed between the core material and the composite material layer. The composite material layer comprises an active substance and a first binder material. The intermediate layer comprises a conductive material and a second adhesive material. The conductive material comprises a first particle with a particle size of 0.005–0.07 μm and forming a beaded aggregate structure, and a second particle with a particle size of 0.5–10 μm and an average aspect ratio of 10–40. The content of the first particle is 1 to 40% by mass of the conductive material. The second adhesive material is mainly composed of thermoplastic resin with a melting point of 100-200°C, and its composition is different from that of the first adhesive material.
3. The electrode according to claim 2, wherein, The content of the second particle is 60 to 99% of the mass of the conductive material.
4. The electrode according to any one of claims 1 to 3, wherein, The content of the conductive material is 50 to 90% of the mass of the intermediate layer.
5. The electrode according to any one of claims 1 to 3, wherein, The first bonding material is a fibrous bonding material. When the composite material layer is divided into three equal parts along its thickness direction, and designated as region 1, region 2, and region 3 starting from the core material side, the content a of the fibrous bonding material in region 1, the content b of the fibrous bonding material in region 2, and the content c of the fibrous bonding material in region 3 satisfy (ca) / (a+b+c)≤±10%.
6. The electrode according to any one of claims 1 to 3, wherein, The conductive material is a carbon material. The thermoplastic resin is a homopolymer or copolymer of vinylidene fluoride.
7. The electrode according to any one of claims 1 to 3, wherein, The second adhesive material is more present around the first particle in the intermediate layer.
8. The electrode according to any one of claims 1 to 3, wherein, The composite material layer contains a conductive material with a particle size of 0.005 to 0.07 μm and forming a beaded aggregate structure.
9. The electrode according to any one of claims 1 to 3, wherein, The electrode is the positive electrode for a secondary battery.
Citation Information
Patent Citations
JP1975098954A
Production of fish meat paste product broiled at high temperature
JP1981048869A
Access control system for loop network
JP1987039936A
Battery electrode and use thereof
CN103168378A
Method for manufacturing electrode for storage element, electrode for storage element, and nonaqueous lithium type electricity storage element
JP2010109080A